Genetic diversity and population structure of the New World screwworm fly from the Amazon region of Brazil - Mastrangelo, Thiago; Fresia, Pablo; Lyra, Mariana L. [UNESP]; Rodrigues, Rosangela A.; Azeredo-Espin, Ana Maria L. (Elsevier B.V., 2014)
Cochliomyia hominivorax (Coquerel) is a myiasis fly that causes economic losses to livestock farmers in warmer American regions. Previous studies of this pest had found population structure at north and south of the Amazon Basin, which was considered to be a barrier to dispersal. The present study analyzed three mitochondrial DNA (mtDNA) markers and eight nuclear microsatellite loci to investigate for the first time the genetic diversity and population structure across the Brazilian Amazon region (Amazonia). Both mtDNA and microsatellite data supported the existence of much diversity and significant population structure among nine regional populations of C hominivorax, which was found to be surprisingly common in Amazonia. Forty-six mtDNA haplotypes were identified, of which 39 were novel and seven had previously been found only at south of Amazonia. Seventy microsatellite alleles were identified by size, moderate to high values of heterozygosity were discovered in all regions, and a Bayesian clustering analysis identified four genetic groups that were not geographically distributed. Reproductive compatibility was also investigated by laboratory crossing, but no evidence of hybrid dysgenesis was found between an Amazonian colony and one each of from Northeast and Southeast Brazil. The results have important implications for area-wide control by the Sterile Insect Technique. Copyright (C) International Atomic Energy Agency 2014. Published by Elsevier B.V. All rights reserved.
Keywords: Cochliomyia hominivorax; Obligate myiasis; mtDNA; Microsatellites